Genderings codes of conduct: Chiquita bananas and Nicaraguan women workers - Larner, Wendy; Prieto-Carron, Marina (Calculating the social: Standards and the reconfiguration of governing, 2010)
All of us have probably eaten Chiquita bananas. Some of us may even remember the Chiquita banana jingle and the blue sticker with Miss Chiquita. Few of us know how the company has engaged with issues of Corporate Social Responsibility (CSR) and the implications for women workers in ‘the very, very tropical equator’ where bananas grow.
https://uqam-bib.on.worldcat.org/oclc/7420757288 https://link.springer.com/chapter/10.1057/9780230289673_3
Keywords: OFDIG; amérique latine; amériques; approches et analyses; femmes*; harcèlement sexuel; nicaragua; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles